DIABETES MELLITUS AND EDUCATIONAL TOOLS IN THE HEALTHCARE SYSTEM - Freitas Macedo, Sthélio; Alves dos Santos, Suenny; Nelson Martins Júnior, Leonidas; da Silva Izidoro, Jaqueline; Guedes de Souza Araújo, Samuel; Passos Vigolvino Macedo, Louise; Gomes de Souza Silva, Lúcia (Revista Gênero e Interdisciplinaridade, 2026)
Diabetes Mellitus is one of the most prevalent chronic diseases in the Brazilian population, requiring effective educational strategies to promote self-care and quality of life. This article aims to analyze the use of pedagogical devices in the care of people with diabetes within the Brazilian Unified Health System (SUS), based on a narrative literature review. Eight articles published between 2018 and 2025 were selected, addressing experiences in health education, interdisciplinary practices, and pedagogical tools aimed at coping with the disease. The results were organized into two thematic categories: (1) health education and the strengthening of self-care in Diabetes Mellitus; and (2) pedagogical devices and the role of the SUS in continuing education. It was found that pedagogical devices – such as discussion groups, workshops, teaching materials, and digital technologies – contribute to the autonomy of users and the humanization of care. However, challenges such as the training of professionals, the valorization of educational practices, and institutional support still limit the reach of these strategies. It is concluded that the incorporation of pedagogical practices in diabetes care should be strengthened as a health promotion policy, in dialogue with the principles of popular education and the Brazilian Unified Health System (SUS).